Students’ Perception on the Use of Grammarly in Thesis Writing - Nursanti, Ida; Salam, Urai; Rezeki, Yanti Sri (Universitas Pamulang, 2025)
This research aims to know students’ perceptions of the use of Grammarly in thesis writing and their experiences in using it. The data were derived from Likert Scale questionnaire and interview. The questionnaire was distributed to 40 English Education students to know about students’ perceptions, which covered three aspects: perceived usefulness, perceived easiness, and students’ satisfaction. Meanwhile, the interview was conducted with three chosen participants to learn about students’ actual experiences in using Grammarly. The result showed the mean score for each aspect with the following distribution: perceived usefulness is 4.06, perceived ease is 3.92, and students’ satisfaction is 4.01. These scores were verbally interpreted as ‘agree’, meaning that students perceived using Grammarly positively. These are supported by the interview results, in which students shared that they experienced benefits from using Grammarly in correcting punctuation, detecting mistyping, reconstructing sentences, and detecting grammar errors. However, the participants also stated that they noticed some weaknesses of this tool, which were related to inaccuracy of the feedback given. Eventually, this study revealed that in general, students agree that Grammarly is a helpful tool to help them with thesis writing, along with its advantages and disadvantages. Therefore, students’ awareness is required to avoid errors that Grammarly might produce.